Interhemispheric Inhibition Induced by Transcranial Magnetic Stimulation Over Primary Sensory Cortex - Iwata, Yasuyuki; Jono, Yasutomo; Mizusawa, Hiroki; Kinoshita, Atsushi; Hiraoka, Koichi (Frontiers in Human Neuroscience, 2016)
The present study investigated whether the long-interval interhemispheric inhibition (LIHI) is induced by the transcranial magnetic stimulation over the primary sensory area (S1-TMS) without activation of the conditioning side of the primary motor area (M1) contributing to the contralateral motor evoked potential (MEP), whether the S1-TMS-induced LIHI is dependent on the status of the S1 modulated by the tactile input, and whether the pathways mediating the LIHI are different from those mediating the M1-TMS-induced LIHI. In order to give the TMS over the S1 without eliciting the MEP, the intensity of the S1-TMS was adjusted to be the sub-motor-threshold level and the trials with the MEP response elicited by the S1-TMS were discarded online. The LIHI was induced by the S1-TMS given 40 ms before the test TMS in the participants with the attenuation of the tactile perception of the digit stimulation (TPDS) induced by the S1-TMS, indicating that the LIHI is induced by the S1-TMS without activation of the conditioning side of the M1 contributing to the contralateral MEP in the participants in which the pathways mediating the TPDS is sensitive to the S1-TMS. The S1-TMS-induced LIHI was positively correlated with the attenuation of the TPDS induced by the S1-TMS, indicating that the S1-TMS-induced LIHI is dependent on the effect of the S1-TMS on the pathways mediating the TPDS at the S1. In another experiment, the effect of the digit stimulation given before the conditioning TMS on the S1- or M1-TMS-induced LIHI was examined. The digit stimulation produces tactile input to the S1 causing change in the status of the S1. The S1-TMS-induced LIHI was enhanced when the S1-TMS was given in the period in which the tactile afferent volley produced by the digit stimulation just arrived at the S1, while the LIHI induced by above-motor-threshold TMS over the contralateral M1 was not enhanced by the tactile input. Thus, the S1-TMS-induced LIHI is dependent on the status of the S1 modulated by the tactile input, and the pathways mediating the sub-motor-threshold S1-TMS-induced LIHI are not the same as the pathways mediating the above-motor-threshold M1-TMS-induced LIHI.